The influence of profitability, liquidity, and capital structure on firm value - Kristianto Bidaya; Mas Intan Purba; Rinahati Laia; Apus Hendri Giawa; Nur Aliah (Journal of Economics and Business Letters, 2023)
This study aims to examine the influence of profitability, liquidity, and capital structure on the value of companies listed on the Indonesian Stock Exchange (IDX) during the period 2018-2021. The population used in this study were food and beverage sub-sector manufacturing companies listed on the IDX over the four-year period from 2018 to 2021, comprising 42 companies. The sample obtained was 17 manufacturing companies listed on the IDX during the 2018-2021 period. The research method used in this study is the quantitative method with multiple linear regression analysis tools, where quantitative data is a study method that is based on conjunctive data. This study uses descriptive statistical tests, Kolmogorov Smirnov statistical tests, multiple linear regression tests, and hypothesis testing with the help of the SPSS 23 program. The results of this study show that profitability partially has a positive and significant effect on the firm’s value, and the variables of liquidity and capital structure simultaneously have no effect on the firm’s value.